Ultratrace Detection of Nickel(II) Ions in Water Samples Using Dimethylglyoxime-Doped GQDs as the Induced Metal Complex Nanoparticles by a Resonance Light Scattering Sensor - Nipaporn Pimsin; Niradchada Kongsanan; Chayanee Keawprom; Phitchan Sricharoen; Prawit Nuengmatcha; Won‐Chun Oh; Yonrapach Areerob; Saksit Chanthai; Nunticha Limchoowong (ACS Omega, 2021)
as a DMG complex with N-GQDs, and the detection was highly sensitive and selective.
Keywords: Carbon and Quantum Dots Applications; Advanced Nanomaterials in Catalysis; Advanced biosensing and bioanalysis techniques